Medroxyprogesterone Acetate Plus Metformin to Prevent Persistent Endometrial Hyperplasia - Vakkas Korkmaz; Enis Özkaya; Tuncay Küçüközkan; Fadıl Kara; Yasemin Çekmez; Hilal Korkmaz (Gynecology Obstetrics & Reproductive Medicine, 2013)
OBJECTIVE: To determine the effect of metformin on treatment response in simple endometrial hyperplasia without atypia. STUDY DESIGN: In this study, we identified 134 women with simple endometrial hyperplasia without atypia. Seventy two of these women were administered cylic oral medroxyprogesterone acetate 10 mg/day for 3 months, 62 of these women were also receiving metformin 1000 mg/day due to preexisting insulin resistance and and all subjects underwent control endometrial sampling after treatment. All subjects were evaluated in terms of age, gravidity, parity, body mass index (BMI), menstrual cycle, luteal phase endometrial thickness, uterine fibroids, ovarian cysts, serum CA 125 levels, systemic disorders, cigarette smoking. All parameters and metformin were assessed for the effects on treatment success. RESULTS: Out of 72 women who were administered medroxyprogesterone acetate 10 mg/day for 3 months, 15 of them were diagnosed as endometrial hyperplasia in control endometrial sampling while only 5 women had persistent endometrial hyperplasia in group with receiving both medroxyprogesterone acetate 10 mg/day and metformin 1000 mg/day (P<0.05). Age, gravidity, serum CA125, BMI, pretreatment endometrial thickness were comparable between groups (P>0.05). CONCLUSION: Medroxyprogesterone acetate and metformin may be used as an adjunctive therapy for persistent endometrial hyperplasias especially in women with high body mass index.